Country of origin effect: evidences from European consumers' of a Brazilian fashion brand - Ronsini Neto, Mário José (2016)
This study aimed to better understand the European consumers’ behavior towards a foreign unfamiliar brand from a developing country based on the real internationalization case study of a Brazilian fashion brand (Osklen). The utilized framework was one of the most studied concepts in International Marketing, the Country of Origin (COO) Effect. This study intended to find evidences of the COO effect on European consumers’ evaluation of a Brazilian brand, based on a sample of students. In order to measure the COO effect on the brand, three survey scenarios were built. In the first scenario the subjects are told that the brand is Brazilian, in the second they are told that the brand comes from the USA and in the third and final scenario there is no cue regarding the origin of the brand. Five hypotheses were proposed and tested based on the literature review. This empirical research has shown that there were statistically significant differences in the evaluation of the Osklen brand by the European consumer, depending on the country of origin informed of the brand, regarding quality, design, reputation and purchase intention. The research has found no connection between the country of origin of the brand and the willingness to pay a higher price for the products of the brand. We have proposed potential strategies that could be utilized by the company following the results of the research.